Marketing determinants of innovation ambidexterity in small and medium-sized manufacturers - Izabela Kowalik; Agnieszka Pleśniak (Entrepreneurial Business and Economics Review (EBER), 2022)
Objective: The study aimed to identify the marketing determinants of SMEs' innovation ambidexterity and explore this phenomenon in the firms from a post-transition Polish market. Specifically, market-sensing capability, entrepreneurial marketing orientation, and marketing strategies were considered the possible determinants of innovation ambidexterity. The comparative character of the study enabled examining if these relationships have changed comparing 2019 to the time of pandemic crisis in 2021. Research Design & Methods: The study includes a sample of 240 Polish manufacturing SMEs contacted with the CATI/CAWI method in May 2019 and 219 firms selected and surveyed according to the same method between January-February 2021. The results were obtained with factor analysis and logistic regression. Findings: Innovation ambidexterity was related to market sensing, opportunity focus, proactive orientation, and adaptation strategy applied by manufacturing SMEs in the B2B markets. However, during the pandemic crisis, the different determinants replaced those identified during the less turbulent time. Implications & Recommendations: Entrepreneurial marketing accompanies innovation ambidexterity. Including employees in the sensing process and concentrating on market opportunities are especially stimulating for exploratory and exploitative innovations. The significant influence of firm size and high-tech industry on ambidexterity points to the role of SMEs' strategic agility in a turbulent environment. Contribution & Value Added: The study explored in detail the marketing determinants of an important SME capability: innovation ambidexterity. Comparing data from the span of two years enabled taking into account the pandemic crisis. In addition, the study verified the measurement tool for analyzing SME ambidexterity.
Keywords: L26; M31; O31; 330; ambidextrous innovation; determinants; entrepreneurial marketing; SME; comparative study